(untitled) (Economics and region, 2025)
This paper examines the impact of Corporate Social Responsibility (CSR) on consumer behavior in Ukraine and globally under the conditions of war. The study explores how companies adapt their social, environmental, and ethical initiatives in response to crisis situations, particularly armed conflicts, and how these adaptations influence consumer preferences and perceptions. Special attention is given to the role of CSR in building trust, fostering consumer loyalty, and maintaining corporate reputation during times of social and economic instability. The study examines global trends in CSR in times of crisis, including support for humanitarian initiatives, reducing the environmental footprint and adherence to ethical standards. The findings reveal that CSR has become a pivotal factor in shaping positive brand perception, influencing consumer choices, and fostering long-term loyalty. Companies that actively engage in socially responsible practices, especially during times of war, are perceived as more trustworthy and aligned with societal values. Moreover, CSR initiatives in Ukraine demonstrate how ethical business practices can contribute not only to corporate success but also to social resilience and community support. Findings indicate that CSR has evolved from a supplementary business strategy into a key determinant of consumer trust and brand perception, especially in unstable environments. Consumers increasingly favor companies that actively contribute to social causes, demonstrate ethical leadership, and support communities in times of distress. Companies that integrate CSR into their core operational strategies are perceived as more responsible, transparent, and aligned with public values. This alignment translates into increased customer loyalty, stronger brand advocacy, and higher levels of engagement.The article shows that in times of war, CSR goes beyond its traditional role as a marketing tool and becomes a mechanism of social influence and a driver of sustainable development. Ultimately, this paper underscores the strategic importance of CSR in shaping modern business practices, particularly in the face of geopolitical crises.